«INTERDISCIPLINARY APPROACH TO THE DIAGNOSTICS OF PATIENTS WITH HIGH-LOWER JOINT DISEASES» - Gafforov Sunnatullo Amrulloevich; Idiev Gayrat Elmuradovich; Kazakova Nozima Nodirovna (Scholar Express Journals, 2021)
In the scientific and practical direction today in the field of dentistry, dysfunction of the temporomandibular joint (TMJ) is considered an urgent problem, that its significance is determined by its high prevalence, difficulty in diagnosis and treatment, a varied and complex clinical picture, requiring a differentiated approach of doctors of various profiles [6 , 7, 8, 13]. According to some literature data, concepts and other theories have been proposed for etiolMGical factors of TMJ patholMGies - these are occlusivearticulatory, myMGenic and monoetiolMGical [3, 5, 14]. According to representatives of the myMGenic theory, the leading role in the pathMGenesis of TMJ dysfunction is assigned to the masticatory muscles [4, 11]; they believe that the joint, jaw and teeth are passive organs that do what muscles dictate. Other authors have found a significant increase in functional disorders of the TMJ due to emotional disorders [9, 12, 16]. The problem becomes even more urgent in the absence of a single algorithm for a comprehensive examination of patients with TMJ patholMGy and parafunction of the masticatory muscles, which is emphasized by domestic and foreign authors [1, 2]. Thus, the analysis of literature data confirms the polyetiolMGical nature of TMJ dysfunction. The development of this disease is directly related to the state of the muscular apparatus, occlusive-articulatory disorders, changes in the height of the lower 1/3 of the face, disorders of neuroendocrine regulation and the emotional sphere
Keywords: LAPAROSCOPIC; SPLENECTOMY; Complications; diseases